Structures élémentaires de la signification - NEF, Frédéric dir. (COMPLEXE, 1976)
CONTENIDO : COLABORADORES BORDRON, JEAN-FRANCOIS; BRANDT, PER-AAGE; COMBET, GEORGES; COURTES, JOSEPH; LIBERA, ALAIN DE; GREIMAS, A.J.; ZILBERBERG, CLAUDE